Comments on eye-flukes (Philophthalmidae Looss, 1819) in the genera Philophthalmus and Natterophthalmus, with a re-designation of the type-species of Natterophthalmus - Radev, Valentin; Kanev, Ivan; Fried, Bernard (Zootaxa, 2006)
A new systematic organization on the eye-flukes of family Philophthalmidae including generic features and keys were published by Kanev et al. (2005). However, that publication contains a mistake (lapsus calami) in the type species information given within the key to the genera of Philophthalmidae. Instead of the original name Natterophthalmus lacrymosus (Braun) n. comb. being used, another name Natterophthalmus hegeneri (Penner & Fried) was listed as the type-species. We apologize for this mistake and would like to provide important but rare and difficult to find information for the future correction of this mistake in the agreement with the International Code of Zoological Nomenclature.